2011
DOI: 10.1007/s11255-011-9905-1
|View full text |Cite
|
Sign up to set email alerts
|

Total, free, and protein-bound thiols in plasma of peritoneal dialysis and predialysis patients

Abstract: Thiol compounds such as glutathione, homocysteine, and cysteinyl-glycine are the natural reservoir of reductive capacity of the cells. Chronic renal failure is accompanied by disturbances in redox status of plasma thiols. The aim of the present study was to compare the changes in concentrations of different forms of thiols in plasma of terminal renal failure patients, nondialyzed and on peritoneal dialysis. Total concentrations of different redox forms of thiols were determined by high performance liquid chrom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…These results indicate that the level of oxidative stress is higher in patients with ESRD than in healthy individuals. Our findings are consistent with previous reports wherein patients with ESRD have been shown to have decreased plasma protein thiols and increased S-thiolated proteins (9,13,14). In addition, Przemysław et al (14) found that the total concentration of glutathione, which is a low molecular weight thiol-tripeptide, was decreased in terminal renal failure patients and that total concentrations of the remaining thiols in these patients were significantly increased compared to those in the healthy subjects.…”
Section: Discussionsupporting
confidence: 93%
“…These results indicate that the level of oxidative stress is higher in patients with ESRD than in healthy individuals. Our findings are consistent with previous reports wherein patients with ESRD have been shown to have decreased plasma protein thiols and increased S-thiolated proteins (9,13,14). In addition, Przemysław et al (14) found that the total concentration of glutathione, which is a low molecular weight thiol-tripeptide, was decreased in terminal renal failure patients and that total concentrations of the remaining thiols in these patients were significantly increased compared to those in the healthy subjects.…”
Section: Discussionsupporting
confidence: 93%
“…Decreased plasma protein thiols and increased S-thiolated proteins have previously been shown in end-stage renal disease patients (13)(14)(15).…”
Section: Introductionmentioning
confidence: 89%
“…Mounting evidence has shown that perturbations in the thiol/ disulfide homeostasis and an oxidative shift in the thiol/disulfide redox potential in plasma are associated with aging and with several different diseases, such as atherosclerosis, chronic renal failure, and preeclampsia [14][15][16][17][18]. However, the complex dynamics of thiol redox status in regulating protein function and gene expression as well as the causal role of thiol dysregulation in disease pathogenesis remain unclear.…”
Section: Introductionmentioning
confidence: 99%